JHEA, Volume 10, n° 2, 2012 - Full Issue - journal system (Journal of Higher Education in Africa, 2012)
Contents Globalizing Higher Education for Neo-liberal Development in Postcolonial Mozambique Adelino Leonardo Chissale ..................................... 1 Aspiring Vice-Chancellors’ Rhetoric and the Challenges of Building a 21st Century Nigerian University Olayiwola Timothy Akinwale & Adeyemi Adegoju .............. 25 Translating Equitable Access into Retention and Success in African Higher Education: The Role and Responsibility of Individual Institutions Sabiha Y. Essack .............................. 47 L’université, un outil de développement local ? Le cas de Jendouba en Tunisie Dhaher Najem .............................. 63 How Women in Higher Education Negotiate Work and Home: A Study of Selected Women at a University in South Africa Deevia Bhana, Venitha Pillay ...................... 81 L’Université de Douala, entre ancrage et désenchantement Louis Roger Kemayou ....................... . 95 Analyse géographique du parcours sciences et techniques : cas de l’Universite de N’gaoundere Mediebou Chindji, Michel Tchotsoua .................... 119 Searching for Balance but Finding Guilt: A Story of Academic Mothers in South Africa Venitha Pillay ...................................... 139